Upper and Lower Weakly $s$-$(τ_1,τ_2)$-continuous Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This article presents new classes of multifunctions called upper weakly $s$-$(τ_1,τ_2)$-continuousmultifunctions and lower weakly $s$-$(τ_1,τ_2)$-continuous multifunctions. Furthermore, several characterizations of upper weakly $s$-$(τ_1,τ_2)$-continuous multifunctions and lower weakly $s$-$(τ_1,τ_2)$-continuous multifunctions are discussed.